Espiral mimética da série Breaking Bad e a narrativa modular hipermoderna - Alves, Adriano Rodrigues (2021)
The series Breaking Bad, created and produced by Vince Gilligan, was broadcast by the American television network AMC between 2008-2013. During its transmission, the series managed to win several prestigious awards, among them, 16 Emmys. The plot addresses issues such as conflict of moral / ethical values in relation to money - family/illness/cancer - drug trafficking. The study intention is to assimilate contemporary narratives, such as modular narrative (CAMERON, 2008), in the series Breaking Bad, in the context of hypermodern society (LIPOVETSKY; SERROY, 2018), more specifically the plot of interactions between characters, especially, Skyler White, Theodore (Ted) Beneke and Walter White, in relation to the Mimetic Theory elaborated by the historian, literary critic, anthropologist, philosopher, theologian, sociologist and French philologist René Girard, which, basically, would be the mimetic character of the intersubjective and interdividual desire of the subject in relation to the Another one that can lead to conflict situations. Therefore, the main interest is to demonstrate the escalation of violence in the narrative as a crescent spiral, which in turn can be transformed into an infinite effect similar to a geometric object of undefined orientation, such as the Möbius Strip and the Bottle of Klein. Wherefore, it was necessary to analyze certain images and transcripts of the episodes of the series Breaking Bad, more specifically of some fragments of the following episodes, namely: season 2 (Episode 7 - “Negro y Azul”; Episode 10 - “Over”; Episode 11 - “Mandala”) to articulate the principles of mimetic desire among the characters; season 3 (Episode 2 - “Horse Without a Name”; Episode 3 - “Sleep with Ted”) to verify the endorsement of interdividuality; and season 4 (Episode 9 - “Listen”; Episode 10 - “Health”; Episode 11 - “Cave”) to demonstrate the occurrence of the “mimetic spiral”. Concomitantly, a survey on modular cinematographic narrative is tensioned, with respect to contemporary narratives, in relation to the changes in our perspectives on time and space regarding hyperart in a hypermodern society. It is worth remembering that this study is not about the “hero's journey”.